Uma poética de restos e de deslocamentos em A República dos Sonhos, de Nélida Piñon - Travia, Nathalia Ribeiro (2022)
This thesis investigates Nélida Piñon's The republic of dreams (2005 [1984]). The novel presents an extensive and complex plot -- concatenated from narratives in which the central theme identified is the question of nationality -- established by the scope of the perspective of three narrators: a female narrator, a male narrator, and an unmarked narrator, in the third person. The republic of dreams is formed with a family space which is known as a dominant space, with its households a combination of Brazilian, Galician, gypsy, and African origins. It was established generations that present, at the individual level, problems about the definitions of the historical-geographical space of a nationality. In other terms, each generation faces, from heterogeneous discursive formations, the question of the integration, reintegration or disintegration of social life. The specific objective is to identify its archives as articulators of stories, voices, and reminiscences of the fictional text to discuss, as a general objective, the constitution of a poetics of remains and dislocations in the relationships between the characters. Hypothetically, in Piñon's text, the space that proposes the theme of nationality is called “the republic of dreams” in which it is argued that fixed files and scattered files (Pedrosa et. al, 2018) are memories of this space. In this sense, the analysis takes up contemporary lines of research linked to gender questions, such as the feminist literary criticism of authors such as Naomi Moniz (1993), Sherry Almeida (2006), Susan Quinlan (2010), Maria González (2016), etc. According to the theoretical-critical categories of Gayatri Spivak (1994), Heleieth Saffioti (2013), and Lélia Gonzalez (2020) highlight the impasse of the (im)possibility of the nationality attribute in the actions of/in the characters. These, in turn, inform, in the activity or the passivity, (dis)locations (BHABHA, 1998) that lead to the poetic treatment given by fixed or dispersed files of memory and consciousness, two themes discussed by Lélia Gonzalez (2020). This work is based on the categories of social ontology, mainly taken up in the realistic ethical-aesthetic thought of György Lukács on aesthetics as alienation or reification, both considered here as dispositive of social consciousness. It is intended to elaborate an analytical interpretation under the perspective of joint reflection on discursive strategies and narrative categories, (de)constructed through the fictional configuration of nationality. As a hypothesis, it is investigated a simultaneous affirmation and transformation of the historical-geographic space through poetics of remains and dislocations in the novel The republic of dreams